Hubungan Antara Strategi Pembangunan Ekonomi dan Keseimbangan Makroekonomi di Indonesia - Muhammad Roykhannul Arif; Isabela Tania; Kiswatul Janah; Riyanti Wahyuni; Gama Pratama (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Economic development strategies play a crucial role in achieving sustainable growth through increased national productivity and equitable welfare distribution. The stability of macroeconomic indicators such as inflation, exchange rates, and gross domestic product growth reflects the effectiveness of government development policies. This study aims to analyze the relationship between economic development strategies and macroeconomic equilibrium in Indonesia by examining the interconnection between the product market and the money market. The research adopts a qualitative approach using literature studies derived from scholarly journals, academic articles, and economic publications obtained from Google Scholar and other credible sources. The findings indicate that maintaining balance between the product market and the money market contributes significantly to national economic stability. A well-coordinated synergy between fiscal and monetary policies is essential to preserve macroeconomic stability and ensure that economic development progresses inclusively and sustainably amid global challenges.